Role of Trees in Farm Bunds – A Case study in Jabalpur district, Madhya Pradesh, India - Dr. S. Saravanan (Indian Journal of Agroforestry, 2023)
Agroforestry systems are multifunctional systems that can provide a wide range of economic, sociocultural and environmental benefits. Agroforestry can be particularly important for smallholder farmers because it generates diverse products and services on a limited land area. The tree resource outside the forest (TOF) is a highly diverse and locally different natural renewable resource. In many regions they play a prominent role in securing rural livelihoods viz., provision of small timber, firewood, fodder, fruits, medicinal value, etc.The present study was conducted at Jabalpur districct of Madhya Pradesh to study the types of tree species being maintained in farm bunds, potential benefits of trees, reason for maintaining trees in bunds, etc. The study reveled that, farmers’ are maintaining around 25 different tree species for various outputs. Marginal farmers are maintaining trees mainly to meet out their daily needs and small and large farmers for future investment. In this paper, the reasons for opting bund planting, level of domestication and adoption and constraints facing by farmers are discussed in detail.